All hands on deck: Co-developing the first international survey of people living with chronic conditions Stakeholder engagement in the design, development, and field trial implementation of the PaRIS survey - Kendir, Candan (OECD Publishing, 2023)
The OECD's Patient-Reported Indicator Surveys (PaRIS) initiative aims to measure outcomes and experiences of healthcare as part of an effort to improve the value of health system investments. The PaRIS survey, a survey of people living with chronic conditions, is currently being implemented in twenty countries. The PaRIS survey has been developed together with government officials, patients, providers, and researchers. However, the extent of stakeholder involvement varies between countries. This paper reports on the stakeholder engagement in design, development and implementation of the PaRIS survey Field Trial in seventeen countries. Engagement strategies were analysed by target group (patients, providers, or other stakeholders), and engagement level (co-designing, involving, consulting, and informing). The results provide valuable lessons for the implementation of the full PaRIS survey in 2023 and illustrate how stakeholders could be more actively engaged in health services research and policymaking
Keywords: Social Issues/Migration/Health; Development